Pengembangan Lembar Kegiatan Peserta Didik Materi Praktikum Akuntansi Lembaga/Instansi Pemerintahan Kelas XII SMK Sebagai Pendukung Integrasi Keterampilan Abad 21 - Sayekti Winarsih; Susanti Susanti (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2021)
The 2013 curriculum is a substitute curriculum for KTSP which has three aspects of assessment which include knowledge assessment, skills assessment, and attitude assessment. This curriculum is competency and character based which integrates learning into four important things, namely strengthening character education, literacy, integration of 21st century skills, and higher order thinking skills. In an effort to increase the skills and knowledge of students, student activity sheets are one of the teaching materials suitable for use in learning. This study aims to develop and analyze the feasibility of teaching materials in the form of Student Activity Sheets for class XII SMK accounting practicum material. The development model used in this research is the 4D development model by Thiagarajan which is limited only to the develop stage. The analysis technique used to process quantitative data in the form of numbers and qualitative in the form of input is a quantitative descriptive technique. Three expert lecturers consisting of accounting education lecturers, Indonesian language lecturers, teaching technology lecturers and one SMK accounting teacher are research subjects that validate the material, language, and graphics of the developed LKPD products. The results of the expert validation showed 88.5% for the material score, language validation with a score of 87.9%, and graphic validation of 92.7% so that the average score obtained was 89.7% with a very feasible category. So that the participant activity sheet is provided with the material for the accounting practicum for government institutions / agencies developed as a support for the integration of 21st century skills in the learning process by students.